Changes in the antioxidant defense system of the body in periodontitis of bacterial-immune genesis and against the background of using metal crowns - Demkovych , A.Ye.; Marfiian , O.V. (Medicni Perspektivi, 2025)
The purpose of this work was to study the effect of fixed prosthetics with metal crowns on the antioxidant defense system of the body in periodontitis of bacterial-immune genesis. The experimental animals were divided into four groups: I – control (n=10); II – animals with periodontitis on the 30th day of the study (n=8); III – animals with periodontitis on the 30th day of the study with stamped crowns (n=8); IV – animals with periodontitis on the 30th day of the study with solid-cast crowns (n=8). Stamped crowns were manufactured by stamping standard sleeves, and cast crowns were manufactured by casting from cobalt-chromium alloy. Experimental bacterial-immune periodontitis was modeled by injecting a suspension of microorganisms (Staphylococcus aureus and Streptococcus haemolyticus) in egg white into the periodontal tissues. To enhance the immune response, rats were additionally administered Freund's complete adjuvant. This procedure was repeated on the 14th day. On the 30th day, blood serum was collected. The activity of antioxidant protection was assessed by the level of superoxide dismutase, catalase, ceruloplasmin and the glutathione system, which were determined by biochemical methods. On the 30th day of periodontitis development, the level of superoxide dismutase decreased by 2.06 times (p<0.001), reduced glutathione by 3.39 times (p<0.001), and catalase and ceruloplasmin increased by 2.70 times compared to the control (p<0.001); by 1.25 times (p<0.01), respectively. After fixation of the stamped crowns, the level of catalase and ceruloplasmin was higher, and superoxide dismutase and reduced glutathione were lower compared to the control. The use of cast structures led to similar changes, but with less severity. Determination of catalase and ceruloplasmin activity in cast crowns showed its decrease by 1.06 times (p<0.05) compared to stamped ones, and the indicators of superoxide dismutase and reduced glutathione were higher by 1.61 times (p<0.01) and by 1.46 times (p<0.001), respectively when using cast structures. Cast crowns showed less negative impact on the antioxidant system compared to stamped ones, which may indicate better biocompatibility of this type of prosthesis.